Further numerical analyses on the solubility of sulfapyridine in ethanol + water mixtures (2016)
Background: Dissolution thermodynamic quantities of sulfapyridine (SP) have been reported in the literature for aqueous alcoholic mixtures. Nevertheless, no attempts to evaluate the preferential solvation of this drug in this binary system, have been reported. In this way, the inverse Kirkwood-Buff integrals (IKBI) were used to evaluate this behavior in solution. Methods: Solubility data for SP dissolved in binary ethanol (EtOH) + water mixtures at various temperatures were mathematically represented using the Jouyban-Acree (J-A) model. The preferential solvation parameters of SP by EtOH (dx1,3) in EtOH + water mixtures were obtained from some thermodynamic properties of the mixtures by means of the IKBI method. Results: Solubility of SP in EtOH + water mixtures is adequately described by the J-A model in second order. Moreover, SP is sensitive to specific solvation effects, so the dx1,3 values are negative in water-rich and EtOH-rich mixtures indicating preferential solvation by water in these mixtures. By contrary, dx1,3 values are positive in the range 0.24 < x1 < 0.53 indicating preferential solvation by EtOH in these mixtures. Conclusion: It can be assumed that in water-rich mixtures the hydrophobic hydration around the aromatic rings plays a relevant role in the solvation. The higher drug solvation by EtOH in mixtures of similar solvent proportions could be due to polarity effects. Moreover, in EtOH + water mixtures SP could be acting as a Lewis acid with the EtOH molecules and in EtOH-rich mixtures the drug could be acting as a Lewis base with water molecules. ©2016 The Authors.